Deteksi Keausan Pahat End Mill Mesin Freis Menggunakan Sinyal Suara - Yogi K Limbong; Feblil Huda (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Wear is the loss of material from the surface of solid objects as a result of mechanical motion. The type of wear that can occur on a machine tool are flank wear and crater wear. Flank wear that occurs on a tool in this case the milling machine can make improper workmanship, damage to the machine, endanger the machine operator, and will cause a decrease in productivity. Observation of the tool condition when not working can be done by measuring using a microscope or measuring the volume of the tool, but this measurement will also reduce the level of production. A system to observe the condition of the tool and detect damage that occurs to the tool and to the working machine is needed to avoid losses that can be caused by tool wear. This system use a microphone as a sensor for the sound singals generated when the engine is working. The signal obtained by the microphone in analog data form is forwarded to the sound card to be converted into digital data. The sound signals were processed by FFT to transfer time domain to frequency domain. The value of magnitude obtained in cutting process with roughing parameters were -40.06 dB at the 1st cut and -37.57 dB at the 33rd cut. magnitude that obtained in cutting process with finishing parameters were -41.51 dB at the 1st cut and -33.98 dB at the 21st cut. Keywords : Milling, Flank Wear, Sound Signal, Fast Fourier Transform, Spectrogram